Effects of Susumeno (skim milk fortified with soy isoflavone and Zn supplement) on menopausal syndrome in premenopausal women - Hery Winarsi; Deddy Muchtadi; Fransiska R Zakaria; Bambang Purwantara (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2004)
Premenopause is part of natural aging process in women indicated by the decrease of ovarial estrogen production, and usually followed by development of menopausal syndrome. Susumeno, skim milk fortified with 100 mg of soy isoflavone and 8 mg of Zn was given to premenopausal women for decreasing menopausal syndrome. This research aimed to evaluate the effect of susumeno on menopausal syndrome in premenopausal women. About 33 premenopausal women aged 43-52 years old in Purwokerto were choosen as respondent. Their menopausal syndrome were identified by using questioner. The answers were scored from 1 to 5 ; i.e., 1 = not detected; 2 = less detected; 3 = mildly detected; 4 = detected; 5 = much detected. It was revealed that some of menopausal syndromes had significantly decreased, especially vaginal dryness from less detected to not detected (p=0,01); fatigue from mildly detected to not detected (p=4,07E-05); mindless from mildly detected to not detected (p=0,022); and dyspareunia from less detected to not detected (p=0,036). Key words: menopausal syndrome, soy isoflavone, Zn, premenopausal women.